2016
DOI: 10.4132/jptm.2016.06.30
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Pathologic Features in Pituitary Adenoma and Correlation with Pituitary Adenoma Recurrence

Abstract: BackgroundThe 2004 World Health Organization classification introduced atypical pituitary adenoma (aPA), which was equivocally defined as invasion with increased mitotic activity that had a Ki-67 labeling index (LI) greater than 3%, and extensive p53 immunoreactivity. However, aPAs that exhibit all of these features are rare and the predictive value for recurrence in pituitary adenomas (PAs) remains uncertain. Thus, we sought to characterize pathological features of PAs that correlated with recurrence.MethodsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The first two factors have already been reported in several studies (13,22,24,28,33). In particular, Kim and coworkers showed that young age and postoperative residue were the two main predictors of recurrence of non-functioning pituitary adenomas (13), and a recent Australian study showed a 4.2-fold greater risk of regrowth or relapse of the tumor in patients younger than 41 years of age (28). Interestingly, we demonstrate for the first time that the proliferative (atypical) character of non-functioning pituitary macroadenoma confers an additional risk of recurrence/progression, with an odds ratio of 4.8, independent of other well-established predictive factors.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The first two factors have already been reported in several studies (13,22,24,28,33). In particular, Kim and coworkers showed that young age and postoperative residue were the two main predictors of recurrence of non-functioning pituitary adenomas (13), and a recent Australian study showed a 4.2-fold greater risk of regrowth or relapse of the tumor in patients younger than 41 years of age (28). Interestingly, we demonstrate for the first time that the proliferative (atypical) character of non-functioning pituitary macroadenoma confers an additional risk of recurrence/progression, with an odds ratio of 4.8, independent of other well-established predictive factors.…”
Section: Discussionmentioning
confidence: 59%
“…We also demonstrated that a younger age, the presence of a postoperative residual tumor and the proliferative nature of the tumor were all independent factors predicting recurrence or progression of NFMA. The first two factors have already been reported in several studies (13,22,24,28,33). In particular, Kim and coworkers showed that young age and postoperative residue were the two main predictors of recurrence of non-functioning pituitary adenomas (13), and a recent Australian study showed a 4.2-fold greater risk of regrowth or relapse of the tumor in patients younger than 41 years of age (28).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A study in 39 patients reported that pituitary adenomas with progression (regrowth within 5 years after initial surgery) had a higher mean proliferation index (3.66% ± 3.00%; n = 12) than tumors without progression (1.89% ± 1.25%; n = 27; P < 0.05) [13]. Other studies have suggested a Ki-67 LI > 3% to be associated with tumor recurrence [14], but others report that although this Ki-67 LI threshold of 3% has a high specificity (89.5%), its sensitivity is comparatively poor (53.8%) [15]. Our study shows that Ki-67 as a standalone parameter is unreliable, in that most of our tumors with high Ki-67 could be fully resected with no visible tumor 3 months after surgery and, therefore, low risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, suprasellar extension and/or cavernous sinus invasion are also not associated with tumor recurrence and, although larger tumors are found to recur more frequently, no statistically significant differences were found. [ 47 ].…”
Section: Resultsmentioning
confidence: 99%